An estimation of the jump of the Milnor number of plane curve singularities - Zakrzewska, Aleksandra (Analitic and Algebraic Geometry 4, 2022)
The jump of the Milnor number of an isolated singularity f0 is the minimal non-zero difference between the Milnor numbers of f0 and one of its deformations fs. We estimate the jump using the Enriques diagram of f0.